THE CLASSROOM PHYSICAL ENVIRONMENT AS A “THIRD TEACHER” FOR AN EARLY CHILDHOOD EDUCATION PROVISION IN THE GA-WEST MUNICIPALITY OF GHANA - Oppong Frimpong, Samuel (PEOPLE: International Journal of Social Sciences, 2019)
In spite of what literature has said about the relevance of the classroom environment and the fact that it can serve as the “Third teacher” in ECE provision, available data shows a lack of infrastructure in most Early Childhood Education (ECE) centres in sub-Saharan Africa, including Ghana. The purpose of this study therefore, was to ascertain a first-hand information about the state of the classroom environment of the ECE centres in the Ga-West Municipality of Ghana and how it was serving as a third teacher for quality ECE provision. Using the convergent design (previously referred to as concurrent triangulation) mixed methods approach, data in the form of questionnaire, interview and observation were collected from 142 participants comprising four ECE circuit coordinators, 130 ECE teachers and four headteachers drawn from 20 schools within the Ga-West Municipality in Greater Accra Region of Ghana. The findings showed some general infrastructural problems in the form of inappropriate furniture, unresourced learning centres and overcrowding classroom space. This possibly limited the ability of some of the teachers to translate their training into classroom practice. It also hindered the role the infrastructure (the classroom environment) could play as a third teacher and how the children could benefit from their classroom environment to aid their learning. Thus, it is recommended that provision should be made to improve on the infrastructure to make it more developmentally appropriate. Additionally, the ECE classroom environment should be carefully arranged to create space to allow for children’s free movement. Tables and chairs used by learners should also be sized to their height and in an appropriate shape (e.g. semi-circle) for their activities and the learning centres should be well resourced and used.